The Concluding Volume of Marx's Capital - Lexis, W. (Quarterly Journal of Economics, 1895)
Journal Article The Concluding Volume of Marx's Capital Get access W. Lexis W. Lexis Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 10, Issue 1, October 1895, Pages 1–33, https://doi.org/10.2307/1884938 Published: 01 October 1895